Nineteenth-Century Co-Production of Knowledge about West Africa. The Case of D’Escayrac and West African Pilgrims - Maguiraga, Siga (Österreichische Zeitschrift für Geschichtswissenschaften, 2023)
Focusing on the cross-cultural interaction between a French traveller and pilgrims from West Africa, this study analyses the actors involved in the construction of European knowledge about West African societies in the mid-nineteenth century. It stresses the role of pilgrims, actors that were often considered peripheral to European knowledge production. The use of the concept of knowledge circulation allows me to explore dimensions of knowledge production such as power relations, resistance, or negotiation, described in the travel account. The paper argues that despite the asymmetries in the pilgrim-traveller relationship, pilgrims co-produced the traveller’s knowledge about West Africa.